Asphyxia due to substandard obstetric care in Finland: An 11-year patient insurance registry study of compensated patient claims - Männistö, Maija; Lojander, Jaana; Welling, Maiju; Axelin, Anna; Härkänen, Marja; Lamminpää, Reeta (Elsevier BV, 2026)
Background
Asphyxia is a major cause of neonatal mortality, often linked to inadequate perinatal care, especially misinterpretation of cardiotocography. In Finland, the Patient Insurance Centre manages medical claims, offering a no-fault compensation model. Utilizing these claims could enhance obstetric safety and newborn health.
Aim
The aim of this study was to analyze the compensated patient claims and identify the substandard care leading to asphyxia.
Methods
A nationwide retrospective registry-based study was conducted. Data included all compensated patient insurance claims for neonatal asphyxia (N = 77) reported to the PIC between 2012 and 2022 Claims involving compensated fetal or neonatal asphyxia were analyzed. Data from the PIC electronic database, including obstetric and neonatal characteristics, severity of asphyxia, interventions, and long-term outcomes, were reviewed, and the substandard care was categorized and analyzed.
Results
Neonatal outcomes were categorized as follows: no permanent injury (n = 26), permanent injury (n = 28), and death (n = 23). All neonates met the criteria for asphyxia, and most required extensive intensive care. Permanent injuries included cerebral palsy, other physical disabilities, and epilepsy. All deaths resulted from severe asphyxia. Substandard care was most often attributed to inadequate monitoring of fetal well-being (n = 69), particularly in using and interpreting cardiotocographs and responding to pathological fetal heart rate changes. Other issues included delayed delivery (n = 64) and inadequate management of the birth (n = 28).
Conclusions
These findings highlight substandard care as a key contributor to asphyxia and emphasize the need for improved clinical practice. Enhancing training, protocols, and quality care standards is crucial to prevent adverse neonatal outcomes.